Vertical Cemetery. (2015) - Hariyono, Wahyu P.
Abstract: Urban cemetery is the city patch where a space that seems far too forgotten has growing up. In large cities, where there is no more vacant land in city center, establishment of new burial has expanded to the periphery or suburb. But there is still no known general method to determine if verticality can also be applied in the future growth of this typology. This could be the alternative thinking to increase the amount without necessarily occupying good available land in cities. Even though in the recent past some architects, such as FilletteRomaric, ChandrasegarVelmourougane, and Martin McSherry have explored these patterns primarily at the architectural scale, systematic research about religion standard and environmental design that investigates the transformation of human needs among these newer forms has not coalesced into a clear way forward. In this research, the idea of skyscrapers that is integrated to cemeteries will also be done by the religion/belief rules comparison in a way of creating spaces. Later, I will translate the previous diagnosis into a classification and typology of spaces that is determined by religion standard and vertical possibilities. By the end of the research, the general urban design proposal for densified cemeteries will be given as the conceptualization conclusion of religion studies and verticality. I expect this new and imaginative approach offers a sustainable solution for urban growth for cities lacking in land.